O-075 Implicit bias in diagnosing mosaicism amongst preimplantation genetic testing providers: results from a large multicenter analysis of 36395 blastocysts. (30th June 2022) - Popovic, M; Lorenzon, A; Sakkas, D; Lledó, B; Parriego, M; Galain, M; Pujol, A; Stoop, D; Rodriguez, M; Pérez de la Blanca, E; Rodríguez, A; Vassena, R
Abstract: Study question: Does the diagnosis of mosaicism affect ploidy rates across different providers offering preimplantation genetic testing for aneuploidies (PGT-A)? Summary answer: Our analysis of 36395 blastocyst biopsies across 8 genetic testing laboratories revealed that euploidy rates were significantly higher in providers reporting low rates of mosaicism. What is known already: Diagnoses consistent with chromosomal mosaicism have emerged as a third category of possible options for embryo ploidy outcomes in PGT-A. However, diagnosing mosaicism using current PGT-A platforms remains hindered by several biological and technical factors. This has led to substantial variability in mosaicism rates amongst genetic testing laboratories. Furthermore, reservations regarding the clinical value of diagnosing mosaicism have led to varying practices in reporting mosaic calls amongst providers. Critically, it remains unknown whether these differences impact the number of euploid embryos available for transfer. Ultimately, this may significantly affect clinical outcomes, with important implications for PGT-A patients. Study design, size, duration: Retrospective, international, multicenter cohort study of 10875 PGT-A cycles conducted between October 2015 and October 2021. A total of 18 IVF centers associated with 8 PGT-A providers, across 5 countries and 3 continents participated in the study, which included 36395 blastocysts, tested using trophectoderm biopsy and next generation sequencing (NGS). Both autologous and donation cycles were assessed. Preimplantation genetic testing for structural rearrangements (PGT-SR) cycles were excluded from the analysis. Participants/materials, setting, methods: Ploidy rates were analyzed using multilevel mixed linear regression. Providers were categorized (A to H), with the most frequent provider used as the reference for statistical analysis. Analyses were adjusted for maternal age, paternal age, donor status, number of embryo biopsied and day of biopsy, as appropriate. The overall significance of categorical variables in the regression models was tested using a Chi-squared test. P-values <0.05 were considered significant. Data analysis was performed using STATA, v.15.0. Main results and the role of chance: The mean maternal age(+SD) across all providers was 36.9(±5.1). As expected, maternal age and day of biopsy had a significant impact on euploidy rates (p < 0.0001). Mosaicism rates were associated with PGT-A provider and independent of all other parameters (maternal age, paternal age, donor status, number of embryos biopsied and day of biopsy). Out of the 8 providers, 7 reported chromosomal mosaicism. Amongst these 7 providers, the rate of mosaic calls varied from 2.9% to 23.9%. After adjusting for confounders, two providers reported significantly higher mosaicism rates compared to the reference (4.2%): Provider-C 10.4% (OR = 2.43, 95%CI: 1.84-4.25) and Provider-F 23.9% (OR = 4.47, 95%CI: 2.92-6.86), while euploidy and aneuploidy rates did not differ. Conversely, the chance of diagnosing mosaicism was lower in Provider-B (OR = 0.34, 95%CI: 0.22-0.54) and Provider-E (OR = 0.59, 95%CI: 0.38-0.90). Here, aneuploidy rates were comparable to the reference, yet the chance of diagnosing a euploid embryo was significantly higher: Provider-B (OR = 2.38, 95%CI: 1.87-3.03) and Provider-E (OR = 1.62, 95%CI: 1.28-2.05). Compared to the reference, euploidy rates were also higher when mosaicism was not reported: 53.5% vs. 44.2% (OR = 2.04, 95% CI: 1.60-2.59). Moreover, the chance of having at least one euploid blastocyst available for transfer significantly increased when mosaicism was not diagnosed (OR = 1.30, 95%CI: 1.13-1.50). Limitations, reasons for caution: Due to the retrospective nature of the study, associations can be ascertained, however causality cannot be established. Certain parameters were not available in the dataset, therefore full elucidation of all potential confounders accounting for the variability may not be possible. Wider implications of the findings: Our findings highlight the significant impact of the genetic testing provider on PGT-A results. We demonstrate that reporting mosaicism primarily comes at the expense of euploid diagnoses, raising concerns regarding the accuracy of mosaicism predictions and their impact on clinical outcomes. Moving forward, greater standardization amongst providers will be essential. Trial registration number: NA